HISTORY OF MUHAMMAD BASIUNI IMRAN AS HEAD OF SHARĪ’AH COURT OFFICE IN THE IMPLEMENTATION OF ISLAMIC LAW IN SAMBAS 1951-1955 WEST KALIMANTAN - Asman; Nur Syamsiah (Jurnal Syariah, 2023)
This article discusses the footsteps of the maharaja Imam Muhammad Basiuni Imran in the application of Islamic law in Sambas, West Kalimantan. Muhammad Basiuni Imran is a charismatic cleric from Sambas with qualified religious knowledge who has several works that are recognized by the Islamic world in reference to Islamic law and has many teachers, one of which is Rasḫid Rihda, a middle eastern cleric who is very famous for his knowledge of legal reform and works he became a reference for world Islamic scholars, especially scholars of the Indonesian archipelago. The focus of this research is how Muhammad Basiuni Imran as the head of the sharī’ah court office in the application of Islamic law in Sambas, West Kalimantan? While the method in this study uses a descriptive qualitative type and the nature of the research is literature. While the approach in this study is to use a historical approach. The findings in this study in the application of Islamic law Muhammad Basiuni Imran were faced with the problem of friday prayer law of less than 40 people, disputes about talkins in society, debates on the issue of marriage faskḥ, developing the concept of masḫlahāh mursālah, the application of the concept of al-Tahāluf al-siyasi and the application of the concept of tadārruj.